Biofabrication of Prevascularised Hypertrophic Cartilage Microtissues for Bone Tissue Engineering - Nulty, Jessica; Burdis, Ross; Kelly, Daniel J. (Frontiers in Bioengineering and Biotechnology, 2021)
Bone tissue engineering (TE) has the potential to transform the treatment of challenging musculoskeletal pathologies. To date, clinical translation of many traditional TE strategies has been impaired by poor vascularisation of the implant. Addressing such challenges has motivated research into developmentally inspired TE strategies, whereby implants mimicking earlier stages of a tissue’s development are engineered in vitro and then implanted in vivo to fully mature into the adult tissue. The goal of this study was to engineer in vitro tissues mimicking the immediate developmental precursor to long bones, specifically a vascularised hypertrophic cartilage template, and to then assess the capacity of such a construct to support endochondral bone formation in vivo. To this end, we first developed a method for the generation of large numbers of hypertrophic cartilage microtissues using a microwell system, and encapsulated these microtissues into a fibrin-based hydrogel capable of supporting vasculogenesis by human umbilical vein endothelial cells (HUVECs). The microwells supported the formation of bone marrow derived stem/stromal cell (BMSC) aggregates and their differentiation towards a hypertrophic cartilage phenotype over 5 weeks of cultivation, as evident by the development of a matrix rich in sulphated glycosaminoglycan (sGAG), collagen types I, II and X, and calcium. Prevascularisation of these microtissues, undertaken in vitro 1 week prior to implantation, enhanced their capacity to mineralise, with significantly higher levels of mineralised tissue observed within such implants after 4 weeks in vivo within an ectopic murine model for bone formation. It is also possible to integrate such microtissues into 3D bioprinting systems, thereby enabling the bioprinting of scaled-up, patient-specific prevascularised implants. Taken together, these results demonstrate the development of an effective strategy for prevascularising a tissue engineered construct comprised of multiple individual microtissue ‘building blocks’, which could potentially be used in the treatment of challenging bone defects.